Mathematics for neuroscientists - 484647 Gabbiani, Fabrizio; Cox, Steven J. (Steven James), 1960- (Amsterdam, NE ; Boston : Elsevier Academic Press, 2010)
Includes bibliographical references (p. 473-482) and index.